The Political Economy of FDI flows into Developing Countries: Does the depth of International Trade Agreements Matter? - Arslan Tariq Rana; Mazen Kebewar (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
There is considerable debate whether the domestic political institutions (specifically, the country's level of democracy) of the host developing country toward foreign investors are effective in establishing the credibility of commitments are still underway, researchers have also analyzed the effect of international institutions such as (GATT-WTO) membership and Bilateral Investment treaties (BIT) in their role of establishing the credibility of commitment to attract foreign investments. In addition, most recent studies have examined the effect of International Trade Agreements (TAs) on FDI flows as they contain separate investment chapters and dispute settlement mechanism, thus providing confidence to investor regarding the security of their investments. We argue that there are qualitative differences among various types of trade agreements and full-fledged trade agreements (FTA-CU) provide credibility to foreign investors and democracy level in the host country conditions this effect whereas the partial scope agreements (PSA) are not sufficient in providing credibility of commitments and not moderated by democracy. This paper analyses the impact of heterogeneous TAs, and their interaction with domestic institutions, on FDI inflows. Statistical analyses for 122 developing countries from 1970 to 2005 support this argument. The method adopted relies on fixed effects estimator which is robust to control endogeneity on a large panel dataset. The strict erogeneity of results by using a method suggested by Baier and Bergstrand (2007) and no feedback effect found in sample. The results state that (1) More the FTA-CU concluded, larger the amount of FDI inflows are attracted into the developing countries and PSA are insignificant in determining the FDI inflow; (2) FTA CU are complementary to democratic regime whereas the conditional effect of PSA with democracy on levels of FDI inflows is insignificant
Keywords: F21; F55; F59; 330; foreign direct investment; free trade agreements; partial scope agreements; domestic institutions